Alumni investment / Arith Syakir Bunsu ... [et al.] - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; -, Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
We all know that information affects market behaviour. Less is known, however, about how information circulates in the market and ultimately influences stock prices. We discovered one method that information spreads and enhances investing success after examining more than 15 year's worth of investment data: through alumni networks. We looked at a sizable data set of mutual fund portfolio managers' trading choices between 1990 and 2006. We contrasted the performance of managers' investments in "connected firms" - companies where at least one senior official attended the same college as the investor - with performance investing in "nonconnected" firms - companies where there were no college connections between the investor and senior ranks.